2021
DOI: 10.3390/pr9071198
|View full text |Cite
|
Sign up to set email alerts
|

Technological Advancement for Efficiency Enhancement of Biodiesel and Residual Glycerol Refining: A Mini Review

Abstract: Biodiesel or known as fatty acid methyl ester (FAME), is a diesel fuel substitute derived from the transesterification reaction of triglycerides with alcohol in the presence of suitable catalyst. The demand for biodiesel is increasing due to environmental and health awareness, as well as diminishing energy security. However, the presence of impurities in biodiesel will affect engine performance by corroding fuel tubes and damaging the injectors. Common methods for the purification of biodiesel include water wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 65 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…The viscosities of the oil were measured using an RST rheometer (product of Brookfield Engineering) as 10 cp and 0.94 cp for the crude oil and normal decane, respectively. The density was measured as 0.83 g/cm 3 (for crude oil) and 0.73 g/cm 3 (for normal decane) at room conditions. The sample preparation was performed with ultrapure water.…”
Section: 1mentioning
confidence: 99%
“…The viscosities of the oil were measured using an RST rheometer (product of Brookfield Engineering) as 10 cp and 0.94 cp for the crude oil and normal decane, respectively. The density was measured as 0.83 g/cm 3 (for crude oil) and 0.73 g/cm 3 (for normal decane) at room conditions. The sample preparation was performed with ultrapure water.…”
Section: 1mentioning
confidence: 99%
“…However, the cost of adsorbents and other additional apparatus makes the process uneconomical. The membrane separation technique, though still largely undeveloped and not commonly used, is environmentally benign, consumes less energy, requires no chemicals, and generates high quality products [ 50 , 51 , 52 ]. The biodiesel generation processes can be intensified by the use of reactor technologies.…”
Section: Modes Of Biodiesel Production In Reactor Technologiesmentioning
confidence: 99%
“…One of the priorities for researchers, designers, and operators of energy systems is the development and effective deployment of clean energy technologies on an industrial scale. This is motivated, in part, by the need to reduce greenhouse gas emissions, which would directly mitigate the fast-progressing climate change [ 1 , 2 ]. Attempts to deploy biofuel production systems on an industrial scale have shown that such technologies are complex process-wise, difficult to maintain, and require high investment costs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%